ANALISIS KEBOCORAN SISTEM REM HIDROLIK PADA MOBIL TOYOTA AVANZA TIPE VELOZ - Gunawan, Gilang Teguh; Nurhaji, Soffan; Suadi, Suadi (Motor Bakar : Jurnal Teknik Mesin, 2023)
We all know that traffic accidents are often caused by the condition of the brake system not working properly which causes the brakes to fail. This study aims to describe the cause of leakage in the hydraulic brake system. The research was carried out with a qualitative approach, the results of which were written in a qualitative descriptive manner. Data collection techniques used observation, literature study, visual inspection, component disassembly and expert assessment at BBPVP Bandung. The results of this study inform that the inspection of the master cylinder components and wheel cylinder components are all still in good condition so that there are no leaks in either the master cylinder or the wheel cylinder. To maintain the performance of the brake system performance, periodic maintenance must be carried out, if the performance of the brake system is not good, immediately check and repair the brake system.